Education in Times of Emergencies Requires Balancing Theory, Practice - Megan Scanlon (The University of Alabama, 2022)
Review of the book: Kevin M. Cahill, editor, Even in Chaos: Education in Times of Emergency. New York: Fordham University Press and The Center for International Humanitarian Cooperation, 2010